UNDIVIDED SUDAN’S OIL PARTNERSHIP WITH INDIA - Dr. Sandipani Dash (Chelonian Research Foundation, 2025)
The expansion of Sudan’s oil sector coincides with rising Asian interest in the oil fields of Africa that is located in the extended supply zone of the present world oil regime. Asian powers have over the years acquired extensive knowledge and experience in domestic oil production; yet that failed to meet their constantly rising energy demands triggered by economic globalsiation. The increasing external dependence pushed these countries to enter into transnational oil ventures. The 9/11 terrorist attack has further propelled the oil-seeking countries to diversify their supply lines by drifting away from West Asia and getting closer to Africa. Asian quest for African equity oil has consequently concretised the Afro-Asian interdependence that has evolved in the post cold war economic world order in terms of trade and investment partnership. As an extension of such economic complemtarity, the current regime in Sudan has diversified the pattern of its transnational production linkage through consolidation of multiple Asian participations in its oil sector. The shift that Sudan’s foreign oil policy behavior has undergone is due to the withdrawal of major Western oil firms, which have initiated the exploration and production activity in its oil field. The underlying rationale for such approach, therefore, lies in the intents to ensure that Sudan’s oil production remains less dependent on the partnership with West, and at the same time to avoid a situation where any single Asian player does monopolise its oil sector. As a result, Asian orientation has become the hallmark of the transnational partnership that Sudan is currently forging for its oil production. This article looks at Sudan’s partnership with India in the broader perspective of Indian interest in African oil. Firstly it taken into account India Presence in Sudan Oil field. Then it explore India Interestent in African Oil field.. Then it examines Sino-Indian Engagement in Sudan’s Oil Sector